An insight into curcumin‐based photosensitization as a promising and green food preservation technology. Issue 4 (9th June 2020) - Seidi Damyeh, Maral; Mereddy, Ram; Netzel, Michael E.; Sultanbawa, Yasmina
Abstract: Consumer awareness on the side effects of chemical preservatives has increased the demand for natural preservation technologies. An efficient and sustainable alternative to current conventional preservation techniques should guarantee food safety and retain its quality with minimal side effects. Photosensitization, utilizing light and a natural photosensitizer, has been postulated as a viable and green alternative to the current conventional preservation techniques. The potential of curcumin as a natural photosensitizer is reviewed in this paper as a practical guide to develop a safe and effective decontamination tool for industrial use. The fundamentals of the photosensitization mechanism are discussed, with the main emphasis on the natural photosensitizer, curcumin, and its application to inactivate microorganisms as well as to enhance the shelf life of foods. Photosensitization has shown promising results in inactivating a wide spectrum of microorganisms with no reported microbial resistance due to its particular lethal mode of targeting nucleic acids. Curcumin as a natural photosensitizer has recently been investigated and demonstrated efficacy in decontamination and delaying spoilage. Moreover, studies have shown the beneficial impact of an appropriate encapsulation technique to enhance the cellular uptake of photosensitizers, and therefore, the phototoxicity. Further studies relating to improved delivery of natural photosensitizers with inherent poor solubility should be conducted. Also, detailed studies on various food products are warranted to better understand the impact of encapsulation on curcumin photophysical properties, photo‐driven release mechanism, and nutritional and organoleptic properties of treated foods.